Análise discursiva da concepção de linguagem do professor de educação infantil - Paiva, Aurikelly Alves de (2012)
We know it is at school that the child day care goer, spend much of their day away from maternal care. In this dynamic space with children and educators the language is experienced.The children attending the nursery begin to live in a school very early, when still in the period of language acquisition. Thus, much of the interaction with the environment is the adult day care, so the teacher will be the significant other to the child, or an interaction matrix. National documents on education emphasize the importance of working language in daycare, but what is the design language of the teacher and how he supports the acquisition of language infans? This work proposes to conduct a discursive analysis of the conceptions of language teacher education. This study investigated the space offered to language, from the teachers' conceptions of language, emphasizing the importance of working with it in the classroom. We sought to identify the design language of the subjects involved in research, and describe the space offered to language in educational practice. For this, we used as the theoretical analysis of the French Discourse (AD) that allowed us to an ideological vision of the speech, as well as the interactionist perspective of Claudia de Lemos who study the issue of language acquisition. In the work by Claudia de Lemos and followers in the IEL, Institute of Language Studies at UNICAMP highlight the work on the Acquisition of Language Pathology and Clinical developed Lael, Applied Linguistics and Language Studies in PUCSP coordinated by Maria Francisca Lier-De Vitto. We emphasize the importance of open space for interaction in the classroom, providing the reader with a reflection on the role of kindergarten teacher with children in daycare in the process of language acquisition. It was observed that the debate on teacher training for early childhood education is insufficient, so no need to progress. With trained professionals can get a better service for children 0-6 years in relation to language. The subjects involved in research value and recognize the importance of working with language and language since the early years